PENGARUH PENDAPATAN ASLI DAERAH, DAU, DAK DAN DANA DESA TERHADAP TINGKAT KEMISKINAN DI INDONESIA TAHUN 2017-2024: PENDEKATAN DYNAMIC PANEL DATA DENGAN SYSTEM GMM - Andriansyah Hasibuan; Arwansyah Arwansyah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the effect of fiscal decentralization instruments, namely Regional Original Income (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Village Fund (Dana Desa), on poverty levels in Indonesia, while simultaneously examining the phenomenon of the poverty trap. This research uses a dynamic panel data approach with the System Generalized Method of Moments (GMM) estimation. The data covers 34 provinces in Indonesia during the period of 2017 to 2024. The results indicate that the poverty level from the previous period has a positive and highly significant effect on current poverty, empirically confirming the existence of a structural poverty trap. Furthermore, PAD and DAU have no significant effect on poverty reduction. In contrast, DAK has a significant negative effect, proving to be the most effective instrument in reducing poverty through targeted basic infrastructure spending. However, the Village Fund shows an anomaly with a significant positive effect on poverty, indicating inefficiency in fund transformation that tends to be consumptive rather than promoting productive economic empowerment. The implication of this study emphasizes the need to reform DAU into a performance-based grant and optimize the Village Fund for human capital enhancement and micro-enterprise empowerment.